PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN CHATIME DI OUTLET CABANG PLAZA SLIPI JAYA - Simatupang, lucy63; Tiara, Ester (Jurnal Manajemen, 2025)
ABSTRACT This study aims to determine whether Brand Image, Product Quality and Price affect Purchasing Decisions at Chatime in Plaza Slipi Jaya. The population in this study were all consumers who made purchases Chatime and the sample in this study was 100 respondents. The design of this study used quantitative methods and the results of this study were based on respondents' answers using a Likert scale. Sampling using non-probability sampling technique. Data analysis method technique in this study was multiple regression linear analysis,simultaneous (F test), partial (t test) and coefficient of determination test (Adjusted R Square) with the help of SPSS 25 software. The results of this study indicate that by simultaneous (F test), there is an influence significant difference between Brand Image, Price, and Promotion on Purchasing Decisions. The partial (t test) shows that Brand Image has a significant effect on Purchase Decisions, Product Quality has not significant effect on Purchase Decisions, and Price has a significant effect on Purchase Decisions.